Blind separation of complex I/Q independent sources with phase recovery - Lin He (2018)
Blind source separation (BSS) techniques allow recovery of individual source signals from observed mixtures, exploiting only the assumption of mutual independence of sources. Generally, complex signals are recovered with an arbitrary phase rotation. In this letter, we propose two BSS algorithms to separate complex sources that have independent in-phase and quadrature (I/Q) parts. The proposed algorithms allow source phase recovery as well as separation. Simulation results demonstrate that the algorithms are effective in recovering source phases without affecting source separation. © 2005 IEEE.